Highly soluble fluorine containing Cu(i) AlkylPyrPhos TADF complexes. Issue 41 (16th September 2019) - Busch, Jasmin M.; Zink, Daniel M.; Di Martino-Fumo, Patrick; Rehak, Florian R.; Boden, Pit; Steiger, Sophie; Fuhr, Olaf; Nieger, Martin; Klopper, Wim; Gerhards, Markus; Bräse, Stefan
Abstract : Newly luminescent Cu(i ) AlkylPyrPhos complexes with a special focus on fluorine have been synthesized and comprehensively investigated by a variety of spectroscopic and theoretical methods. Abstract : Luminescent Cu(i ) AlkylPyrPhos complexes with a butterfly-shaped Cu2 I2 core and halogen containing ancillary ligands, with a special focus on fluorine, have been investigated in this study. These complexes show extremely high solubilities and a remarkable (photo)chemical stability in a series of solvents. A tunable emission resulting from thermally activated delayed fluorescence with high quantum yields was determined by luminescence and lifetime investigations in solvents and solids. Structures of the electronic ground states were analyzed by single crystal X-ray analysis. The structure of the lowest excited triplet state was determined by transient FTIR spectroscopy, in combination with quantum chemical calculations. With the obtained range of compounds we address the key requirement for the production of organic light emitting diodes based on solution processing.